Prevalence and associated factors of severe malaria-hemoglobinuria among children below 15 years: A retrospective cross-sectional study at a tertiary regional referral hospital in Uganda. (Student's Journal of Health Research Africa, 2025)
Background: The World Health Organization (WHO) report of 2022 showed that Uganda accounted for 5.1% of the global case burden. Severe malaria presenting with hemoglobinuria is characterized by tea coloured urine, jaundice, and anemia. This study aimed to understand the prevalence and associated factors of severe malaria-hemoglobinuria among children below 15 years admitted to a tertiary hospital in Uganda. Methods:A retrospective study that involved reviewing patient files of children aged 15 years and below admitted at Kayunga regional referral hospital in Uganda during 2023. Data was extracted using a standardized checklist developed according to the WHO 2015 clinical surveillance criteria for severe malaria. Sociodemographic, clinical, and laboratory data were collected and analyzed using Stata 18. Logistic regression analysis was used to evaluate the factors associated with severe malaria-hemoglobinuria. A p-value
Keywords: Severe Malaria; Haemoglobinuria; Paediatric; Black-water fever